OBTAINING THE OCEAN TIDE FROM GNSS POSITIONING ALLIED TO DATA FILTERING METHODS - Silva, Valder Alvaro da Luz [UNESP]; Alves, Daniele Barroca Marra [UNESP]; Setti, Paulo T.; Santana, Felipe Rodrigues (FapUNIFESP (SciELO), 2024)
The evolution of Global Navigation Satellite System (GNSS) positioning has greatly benefited several areas of knowledge. For Hydrography, an application improved by this science is the measurement of sea level oscillations resulting from tides. However, to satisfactorily retrieve this information, it is necessary to use low-pass filters (LPF) to match high frequency signals resulting from variation of the vertical component of the GNSS positioning to those of low frequency that characterizes tidal waves. Currently, there is a wide variety of LPF, which are selected according to the required purpose. Thus, the objective of this study is to obtain tidal height variations with high accuracy by applying LPF in GNSS positioning vertical coordinates tracked by an onboard GNSS receiver. For this purpose, field research and the processing of obtained data was performed. Then, two data filters were tested: the Simple Moving Average (SMA) Filter and wavelet compression. In both options, the results reached centimetric accuracy when compared to the real tide in the region of study. However, through quantitative and qualitative evaluations, it was verified that the SMA filter was considered more advantageous because, in addition to its high accuracy, it has a simpler application and less expensive in computational terms.
Keywords: GNSS; Positioning; PPK; SMA Filter; Tides; Wavelet